Sustainable livelihoods from tourism in the "10 New Balis" in Indonesia. Issue 6 (3rd June 2021) - Westoby, Ross; Gardiner, Sarah; Carter, R. W. (Bill); Scott, Noel
ABSTRACT: The "10 New Balis" aims to duplicate the economic effects of tourism in Bali to 10 new tourism destinations in Indonesia. Group interviews were conducted with Indonesian tourism stakeholders ( N  = 22) to investigate aspirations, deficits and tensions in these destinations. Findings show that human capital development in regional areas is needed to avoid tensions from top-down, elite-led development, as well as training to achieve sustainable livelihood outcomes. Tourism infrastructure is also needed to support tourism development, but this needs to be balanced by the associated impacts. A framework is put forward for Indonesia's tourism potential or threat to sustainability.